Awareness of retinal screening in patients with Type 2 diabetes mellitus: Are we meeting standards of care? - Adil, Munazir; Siddiqui, Samreen; Waghdhare, Swati; Bhargava, Amit; Jha, Sujeet (Asian Journal of Medical Sciences, 2017)
Background: Since diabetic retinopathy is a silent, but progressive complication of diabetes, and comprises 4.8% of the global causes of blindness, it is imperative that it is detected early and treated in a timely fashion.Awareness about retinopathy amongst patients with diabetes is an important aspect in the management of diabetes. Aims and Objective: To understand the level of awareness of retinal screening in North Indian patients with diabetes mellitus (DM), attending a tertiary care hospital. Materials and Methods: This was an observational, cross-sectional questionnaire based study, conducted over a 6 month period at a tertiary care hospital in North India. Patients above the age of 18, having an underlying diagnosis of type 1 diabetes mellitus (T1DM) or type 2 diabetes mellitus (T2DM), were included in the study. The Unpaired or independent student t-test were used for the comparison of the mean value of two groups, and the Chi-square test for the comparison of categorical variables. The p-value was taken as significant when less than 0.05 (p<0.05). A Confidence interval of 95% was used. Results: The mean age of the study subjects was 53.78±11.24 years, with a mean age of diagnosis of 46.50±10.7 years, and a mean duration of having diabetes of 7.4±7.61 years. Glycemic control was sub-optimal, with the mean HbA1c of the cohort at 9.55%. Of 100 responders, 33% reported being unaware of the ocular complications of diabetes. Only 48% stated that their healthcare provider had advised them that they need a routine yearly dilated eye exam. Despite 62% of the cohort reporting decreased visual acquity, 52% did not have an eye exam in the preceding year. Conclusion: The majority of our patients remains unaware of the complications of their diabetes, and hence may not be engaged in its management. More longitudinal studies are needed to understand what factors are affecting health literacy in the population. Better sustainable and patient-centric education models need to be developed, that will serve to increase health literacy, and improve patient care. Asian Journal of Medical Sciences Vol.8(6) 2017 9-12